PENGARUH PERJANJIAN UTANG BERBASIS AKUNTANSI (ACCOUNTING BASED COVENANT) PADA PERINGKAT OBLIGASI YANG DITERBITKAN OLEH PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI - Hiqmahtunnisah Hiqmahtunnisah; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
AbstractThis study aims to determine the effect of accounting based covenant(leverage, profitability and firm growth) toward bond rating. The sample ofthis study are LQ45 companies listed in Indonesian Stock Exchange (IDX)during the period 2013-2016. The sampling technique used was purposivesampling, in order to get as many 17 companies.This study uses secondary data obtained from Indonesian StockExchange, technical analysis of the data used is the multiple linearregression analysis with the help of SPSS software.The result of the research show that the variable of leverage,profitability, and firm growth significant positive effect on bond rating.Keyword: accounting based covenant, leverage, profitability, firm growthand bond rating